PERBEDAAN HASIL BELAJAR SISWA DALAM MATERI SENI RUPA YANG MENGGUNAKAN MEDIA VIDEO MELALUI POWER POINT DENGAN MEDIA KONVENSIONAL DI SMAN 1 PALEMBAYAN - YELNI RAHMADILA, Drs. Eswendi,M.Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
This research aimed to found students achievement in fine art material through power point with conventional media in SMAN 1 Palembayan. The research was a quantitative approach quasi exsperiment method, within nonequivalent control group design program. The researcher used test technique to collect the data. Then, the data were analyzed by descriptive technique within t-test formula (paired sample t test). The result showed that there was differences students achievement in learning fine art that used video media through power point by conventional media in SMAN 1 Palembayan, with other word using power point on students class X SMAN 1 Palembayan increase learning achievement.Kata Kunci: hasil belajar, materi seni rupa, media video melalui power point